Efficacy and safety of brolucizumab in age‐related macular degeneration: A systematic review of real‐world studies. Issue 2 (18th September 2022) - Baumal, Caroline R.; Sørensen, Torben Lykke; Karcher, Helene; Freitas, Rita L.; Becher, Anja; Balez, Sébastien; Clemens, Andreas; Singer, Michael; Kodjikian, Laurent
Abstract: Intravitreally injected anti‐vascular endothelial growth factor (anti‐VEGF) agents are first‐line treatment for neovascular age‐related macular degeneration (nAMD). Phase 3 trials demonstrated non‐inferiority of anti‐VEGF therapy with brolucizumab compared with aflibercept in best corrected visual acuity (BCVA) gains, with superior anatomical outcomes after brolucizumab. The purpose of the review was to summarize real‐world efficacy and safety data on brolucizumab in patients with nAMD. The review protocol was registered with PROSPERO (ID: CRD42021290530). We conducted systematic searches in Embase, Medline and key ophthalmology congress websites (19 October 2021). Original reports of efficacy and/or safety in patients receiving brolucizumab to treat nAMD in clinical practice were eligible. The descriptive summary includes reports describing at least 10 brolucizumab‐treated eyes. In total, 2907 brolucizumab‐treated eyes from 26 studies were included. Outcomes were available for treatment‐naive eyes (six studies), eyes switched to brolucizumab from other anti‐VEGFs (16 studies), and/or treatment‐naive and switch eyes combined (eight studies). Follow‐up time points ranged from 4 weeks to 1 year post‐brolucizumab initiation. For BCVA, significant improvements compared with brolucizumab initiation were reported in four of six studies in treatment‐naive eyes (mean BCVA improvement, range: +3.7 to +11.9 Early Treatment Diabetic Retinopathy Study [ETDRS] letters) and in three of 12 studies in switch eyes (range: +9.0 to +15 ETDRS letters) (all p < 0.05); remaining studies reported no significant post‐brolucizumab BCVA changes. For central subfield thickness (CST), improvements post‐brolucizumab initiation were reported in all six studies in treatment‐naive eyes (mean CST improvement, range: −113.4 to −150.1 μm) and in eight of 11 studies in switch eyes (range: −26 to −185.7 μm) (all p < 0.05). The 14 studies reporting on intraretinal, subretinal and/or total fluid observed improvements post‐brolucizumab initiation. The four studies comparing treatment intervals observed extension of the interval between injections after switching to brolucizumab from other anti‐VEGFs. Incidence of intraocular inflammation ranged from 0% to 19%. In conclusion, real‐world efficacy and safety data concur with brolucizumab pivotal trials. Additionally, reduction of disease activity in anti‐VEGF switch eyes was demonstrated by fluid reduction and/or visual acuity gain, along with prolongation of the interval between injections.